Peningkatan Parameter Mekanis Tanah Lempung Plastisitas Tinggi sebagai Bahan Timbunan dengan Penambahan Kapur - Yusti Yudiawati; Nur Fitriah (Fakultas Teknik, 2022)
The clay plasticity can be reduced chemically using lime which contains Ca++ and Mg++ to neutralize the swelling and shrinkage properties. The test soil sample from Teluk Mesjid Village, Balangan Regency, has a 51% liquid limit, a 30.45% plastic limit and 20.55 Plastic Index, it is not specified as an embankment material. The lime percentage was based on plasticity test on soil mixed with 4%, 6% and 8% lime. Direct shear and independent compressive strength tests were carried out on the original soil samples and soil samples with addition of 6% lime resulting from standard and modified compaction as well as CBR tests for unsoaked and soaked conditions. The lime addition reduced the Plasticity Index greatly from 20.55% to 5.84% or to low plasticity category. Soil cohesion increased up to 100%. The shear angle increased was only 2-3°. The ultimate bearing capacity of the free compression test from modified compaction increased significantly up to 100%. The increase in CBR value in soaked conditions reached 59.6% to 63%. The soaked CBR value with lime addition increased from 7% to 17.4% or increased for 2.48 times.